Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Given the identically distributed and independant random variables $X_1,X_2,\ldots\sim\operatorname{Po}(\lambda)$ and $S_n=X_1+\ldots+X_n$ show with induction that $$\Pr[S_n=k]=\frac{(n\lambda)^k}{k!}e^{-n\lambda}.$$

So far for $n=1$ via the definition of the density function for Poisson:$$\Pr[S_1=k]=\Pr[X_1=k]=\frac{e^{-\lambda}\lambda^k}{k!}$$ With $n=2$ and independency: $$\Pr[X_1+X_2=k]=\sum\limits_{n=0}^k\Pr[X_1=n]\Pr[X_2=k-n]=\sum\limits_{n=0}^k\frac{\lambda^n}{n!}e^{-\lambda}\frac{\lambda^{k-n}}{(k-n)!}e^{-\lambda}$$$$=\frac{1}{k!}e^{-2\lambda}\sum\limits_{n=0}^k\binom{k}{n}\lambda^n\lambda^{k-n}=\frac{(2\lambda)^k}{k!}e^{-2\lambda}$$ I assume now that with $S_n\sim\operatorname{Po}(\lambda)$ every $X_i\sim\operatorname{Po}(\lambda/n)$ and every Poisson variable can obviously split up, but how can I prove this?

share|cite|improve this question
up vote 2 down vote accepted

Assume that the sum of $m$ independent Poisson with parameter $\lambda$ is Poisson with parameter $m\lambda$. We show that the sum of $m+1$ independent Poisson with parameter $\lambda$ is Poisson parameter $(m+1)\lambda$.

You post basically does it: exactly the same reasoning that got you from $1$ to $2$ gets you from $m$ to $m+1$.

Using almost exactly your notation, we find that $$\Pr(S_{m+1}=k)=\sum\limits_{n=0}^k\Pr(S_m=n)\Pr(X_{m+1}=k-n)=\sum\limits_{n=0}^k\frac{(m\lambda)^n}{n!}e^{-m\lambda}\frac{\lambda^{k-n}}{(k-n)!}e^{-\lambda}.$$ It follows that $$\Pr(S_{m+1}=k)=\frac{1}{k!}e^{-(m+1)\lambda}\sum\limits_{n=0}^k\binom{k}{n}(m\lambda)^n\lambda^{k-n}=\frac{((m+1)\lambda)^k}{k!}e^{-(m+1)\lambda}$$

The last equation is by the Binomial Theorem. For $$\sum_{n=0}^k \binom{k}{n}x^ny^{k-n}=(x+y)^k.$$ We are putting $x=m\lambda$ and $y=\lambda$, so $x+y=(m+1)\lambda$.

share|cite|improve this answer
Oh yep, so close... but it works! – Christian Ivicevic Jun 25 '12 at 14:43
Using characteristic functions is also an option, since they are independent the char of the sum is just the multiplication of the chars, which are equal. – Jorge E. Cardona Nov 28 '13 at 18:04
@JorgeEduardoCardona: That would indeed be a very good way. From the wording of the question, it is likely not to be the intended way. Another way which I prefer is to show that the sum of independent Poisson satisfies the "axioms" under which one concludes that a random variable is Poisson. – André Nicolas Nov 28 '13 at 18:11

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.